Democracy from Scratch : Opposition and Regime in the New Russian Revolution - Fish, M. Steven (Book collections on Project MUSE., 2001)
This book presents a fresh view of Russian political change in the Gorbachev and early post-Soviet periods not by examining perestroika and glasnost in and of themselves, but by investigating the autonomous political organizations that responded to liberalization. Extensive study of these political groups, in Moscow and several provincial cities, has led M. Steven Fish to conclude that they were shaped to a far greater degree by the nature of the Soviet state than by socioeconomic modernization, political culture, native psychology, or Russian historical tradition. Fish's statist theory of soc.